Jane foster the saga of the mighty thor ebook - Aaron, Jason (Jane Foster: The Saga Of The Mighty Thor., 2022)
Collects Thor (2014) #1-8; Thor Annual (2015) #1 (B story); Mighty Thor (2015) #1-5, 8-11, 13-14; Generations: Unworthy Thor and Mighty Thor (2017) #1. Goddess of Thunder! When the Odinson is rendered unworthy of lifting Mjolnir, another claims the hammer! Her battles against Frost Giants, Malekith and the Minotaur prove she's well worthy of the name Thor! But this new hero is secretly Dr. Jane Foster - and each time she transforms, it worsens the cancer that's killing her! As the Odinson comes to terms with the loss of his hammer, the new Thor defines her independence when she battles Odin himself! But will she prevail when she's caught between Roxxon and S.H.I.E.L.D.? Meanwhile, Malekith is waging war across the realms - and Jane must lead a powerful new team to oppose his terrible plans!